THE FORMATION OF CHILDREN’S CHARACTER IN ISLAM: AN ANALYSIS OF SURAH LUQMAN VERSES 13–16 - Anggraini, Fitri; Razzaq, Abdur; Imron, Kristina (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores the formation of children’s character in Islam through a thematic analysis of Surah Luqman verses 13–16. The background of this research is rooted in the increasing moral degradation among Indonesian children, which is manifested in various alarming behaviors such as violence, juvenile delinquency, immorality, bullying, and conflicts within educational institutions. These conditions highlight the urgency of integrating spiritual-ethical values into character education in a more systematic, sustainable, and transformative manner. The aim of this research is to formulate a comprehensive conceptual understanding of Quranic-based character formation and to examine its pedagogical implications for contemporary Islamic education. This study employs a qualitative library research method using content analysis of primary sources—including the Qur’an, classical and modern tafsir, and relevant hadith—as well as secondary sources such as academic books, peer-reviewed journals, and prior empirical studies. The findings reveal that Luqman’s counsels to his son present a multi-dimensional framework of character formation comprising: (1) tawhid education as the core spiritual foundation that warns against polytheism and its ethical consequences; (2) filial piety (birr al-wālidayn) which promotes moral responsibility toward parents while upholding theological principles; and (3) spiritual consciousness of divine surveillance, emphasizing that every human action—no matter how small—is accountable before God. The study concludes that effective implementation of Islamic character education requires a holistic approach that integrates spiritual, cognitive, emotional, and social dimensions through exemplary conduct, consistent habituation, and constructive communication. Furthermore, the collaboration among family, educational institutions, and the broader community serves as a decisive factor in nurturing a morally upright and resilient young generation. This research contributes a systematic conceptual model for strengthening character education based on Islamic values in addressing contemporary moral challenges.